Clinical and Microbiologic Follow-Up Evaluations After Non-Surgical Periodontal Treatment With Erbium:YAG Laser and Scaling and Root Planing - Valerio Lopes, Beatriz Maria [UNESP]; Theodoro, Letícia Helena [UNESP]; Melo, Rafaela Fernanda [UNESP]; de Azevedo Thompson, Gloria Maria [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (Amer Acad Periodontology, 2010)
Background: This study compared erbium-doped: yttrium, aluminum, and garnet (Er:YAG) laser irradiation (100 mJ/pulse; 10 Hz; 12.9 J/cm(2)) with or without conventional scaling and root planing (SRP) to SRP only for treatment of periodontal pockets.Methods: Nineteen patients with pockets from 5 to 9 mm were included. In a split-mouth design, each site was allocated to a treatment group: 1) SRPL, SRP and laser; 2) L, laser; 3) SRP, SRP only; and 4) C, no treatment. Clinical parameters of probing depth (PD), gingival recession, and clinical attachment level (CAL) were evaluated at baseline and 1, 3, 6, and 12 months after treatment. Visible plaque index, gingival bleeding index (GI), bleeding on probing (BOP), and subgingival plaque samples were also measured 12 days postoperatively, in addition to the above mentioned months. Intergroup and intragroup statistical analyses were performed (P<0.05).Results: GI decreased for SRPL and increased for L, SRP, and C (P <0.05) 12 days postoperatively and decreased for SRPL and SRP (P <0.05) 3, 6, and 12 months after baseline; BOP and PD decreased for all treated groups (P<0.01) 3, 6, and 12 months after treatment. CAL gain was significant for SRPL, L, and SRP (P<0.05) 3, 6, and 12 months postoperatively. SRPL and L presented a significant reduction in the percentage of sites with bacteria 6 and 12 months after treatment (P<0.05).Conclusion: Non-surgical periodontal treatment with Er:YAG laser may be an alternative treatment for reduction and control of the proliferation of microorganisms in persistent periodontitis. J Periodontol 2010;81:682-691.
Keywords: Clinical trial; lasers; periodontitis; scaling and root planing